2022
DOI: 10.1186/s13195-022-01145-x
|View full text |Cite
|
Sign up to set email alerts
|

A low-dimensional cognitive-network space in Alzheimer’s disease and frontotemporal dementia

Abstract: Background Alzheimer’s disease (AD) and frontotemporal dementia (FTD) show network dysfunctions linked with cognitive deficits. Within this framework, network abnormalities between AD and FTD show both convergent and divergent patterns. However, these functional patterns are far from being established and their relevance to cognitive processes remains to be elucidated. Methods We investigated the relationship between cognition and functional connec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Furthermore, these phenotype geometries readily relate to everyday clinic observations to explain variation across canonical presentations and clinical “chameleons” 32 such as bvFTD with AD-like severe amnesia 33,34 or FTLD-motor syndromes with aphasia, 35 accommodate locations of broad categorical descriptors such as “mixed aphasia” or “atypical dementia”, and relate them to different neural-pathological mechanisms. 31,36,37 In short, leveraging phenotypic heterogeneity to clinical advantage remedies limitations of categorical-only descriptive approaches, models fluid intersections and dynamic trajectories of syndromes, and reveals the large landscape of nuanced inter-individual clinical variations in AD/FTLD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these phenotype geometries readily relate to everyday clinic observations to explain variation across canonical presentations and clinical “chameleons” 32 such as bvFTD with AD-like severe amnesia 33,34 or FTLD-motor syndromes with aphasia, 35 accommodate locations of broad categorical descriptors such as “mixed aphasia” or “atypical dementia”, and relate them to different neural-pathological mechanisms. 31,36,37 In short, leveraging phenotypic heterogeneity to clinical advantage remedies limitations of categorical-only descriptive approaches, models fluid intersections and dynamic trajectories of syndromes, and reveals the large landscape of nuanced inter-individual clinical variations in AD/FTLD.…”
Section: Introductionmentioning
confidence: 99%
“…The VAN’s role in detecting and filtering relevant information from the environment, as well as its involvement in attention shifting and salient stimulus processing, has been consistently reported in prior studies [42, 43]. BV-FTD exhibited significant alterations in VAN connectivity compared to HCs and showed even more profound disruptions in VAN than AD, possibly due to the VAN’s association with psychiatric disorders [11, 20, 41]. Similarly, the VAN exhibited dysconnectivity in SV-FTD compared to HCs [44, 45].…”
Section: Discussionmentioning
confidence: 65%
“…Disruptions in these networks, DMN, FPN, and VAN, have been described as a “triple model” observed in various diseases, including autism, schizophrenia, and AD [40]. This model suggests that the VAN acts as an interface between the DMN and FPN, regulating their competing inter-network activities and promoting appropriate behavioral responses [40, 41]. Our intra- and inter-module analyses identified altered connectivity patterns within the VAN, such as VAN-AN, VAN-DMN, and VAN-SUB.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alzheimer's disease and dementia exhibited bidirectional causal relationships with fMRI traits and DTI parameters. Prior studies have consistently reported that resting fMRI connectivity patterns are disrupted in patients with Alzheimer's disease 101,102 , particularly in brain regions involved in memory and cognitive function 103,104 .…”
Section: Intra-brain Causal Connectionsmentioning
confidence: 99%